Formulation and characterization of cassava starch film incorporated with kaffir lime peel oil - Mohammed Manshor, Norasmah (2024)
Packaging materials from synthetic polymer leads to a rise in solid waste, contributing to environmental pollution. In addition, food products require protection against microbial spoilage. Therefore, the development of biopolymer film from cassava starch incorporated with Citrus hystrix oil as antimicrobial agent, also known as kaffir lime oil, for food packaging application was presented in this study. In the present work, the aims were to determine the bioactive compounds in kaffir lime oil, to determine the properties of film solution and characterization of the film, as well as the moisture sorption isotherm of the film and its mathematical model.